909 Haplotype-specific chromatin looping reveals genetic interactions of regulatory regions modulating gene expression at the SLE susceptibility locus FAM167A-BLK. (14th December 2022) - Ribeiro, Mariana Saint-Just; Tripathi, Pulak; Namjou, Bahram; Harley, John B; Chepelev, Iouri
Abstract : A major goal of genetics research is to elucidate mechanisms explaining how genetic variation contributes to phenotypic variation. The genetic variants identified in genome-wide association studies (GWASs) generally explain only a small proportion of heritability of phenotypic traits, the so-called missing heritability problem. Recent evidence suggests that additional common variants beyond lead GWAS variants contribute to phenotypic variation; however, their mechanistic underpinnings generally remain unexplored. Herein, we undertake a study of haplotype-specific mechanisms of gene regulation at 8p23.1 in the human genome, a region associated with a number of complex diseases. The FAM167A-BLK locus in this region has been consistently found in the genome wide association studies (GWASs) of systemic lupus erythematosus (SLE) in all major ancestries. Our haplotype-specific chromatin interaction experiments, allele-specific enhancer activity measurements, genetic analyses and epigenome editing experiments revealed that: (1) haplotype-specific long-range chromatin interactions are prevalent in 8p23.1; (2) BLK promoter and cis -regulatory elements cooperatively interact with haplotype-specificity; (3) genetic variants at distal regulatory elements are allele- specific modifiers of the promoter variants at FAM167A-BLK ; (4) the BLK promoter interacts with and, as an enhancer-like promoter, regulates FAM167A expression and (5) local allele-specific enhancer activities are influenced by global haplotype structure due to chromatin looping. Although SLE causal variants at the FAM167A-BLK locus are thought to reside in the BLK promoter region, our results reveal that genetic variants at distal regulatory elements modulate promoter activity, changing BLK and FAM167A gene expression and disease risk. Our results suggest that global haplotype-specific 3-dimensional chromatin looping architecture has a strong influence on local allelic BLK and FAM167A gene expression, providing mechanistic details for how regional variants controlling the BLK promoter may influence disease risk.